Defining the role of cerebellar output circuits in food-seeking behaviour - Ho, Helen Shen Ting (2018)
The cerebellum modulates motor learning and coordination, as well as non-motor functions such as motivation and feeding control. Lesion and perturbation in the cerebellum are linked to disruption of feeding behaviour in rodent and human studies, but details about cerebellar-mediated pathways that control feeding is not well defined. The current study utilises molecular genetics and behavioural analysis in mice to examine the contribution of neuronal subpopulations of neurons in the deep cerebellar nuclei (DCN) in food-seeking behaviours and to delineate the circuit elements involved. Viral mapping of the connectivity of the DCN with extra-cerebellar regions revealed that these output neurons are indirectly linked to the arcuate nucleus of the hypothalamus, which is an important modulator of hunger responses. A major target of the DCN, zona incerta, receives cerebellar input and then project to the arcuate nucleus. To examine the functional relevance of this pathway, we have employed a chemogenetic strategy in mice to selectively and acutely manipulate the activity of DCN neurons. The activation of DCN neurons results in appetite loss and reduced food-seeking behaviour in mice, and opposite results are observed when DCN is activated. To determine whether neuronal subpopulations in the DCN differentially regulate feeding, we have correlated the feeding response of manipulated mice to subnuclei of the DCN including IntDL, Lat and IntPC. Together, we defined the connectivity and functional relevance of a pathway linking the cerebellum and hypothalamus, and provide insight into how perturbation of a cerebellar output circuit could lead to disrupted feeding behaviour.